1998
DOI: 10.1111/j.1574-6941.1998.tb00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the community structure of wastewater treatment plants: a comparison of old and new techniques

Abstract: Wastewater treatment is a process of increasing importance in a world with an ever growing human population. Today, most wastewater treatment processes make use of the natural self‐purification capacity of aquatic environments which is the result of the presence and action of microbial communities. Consequently, wastewater treatment facilities are designed to maintain high densities and activities of those microorganisms that satisfy the various purification demands. The performance, at least of large plants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(67 citation statements)
references
References 50 publications
1
66
0
Order By: Relevance
“…Other studies have also demonstrated that the complex structure of activated sludge systems is difficult to assess with traditional techniques (2,3). The range of emerging molecular techniques used to investigate systems in situ may not completely replace traditional microbiological techniques but will help to identify, monitor, and isolate important organisms in wastewater systems (24,30).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also demonstrated that the complex structure of activated sludge systems is difficult to assess with traditional techniques (2,3). The range of emerging molecular techniques used to investigate systems in situ may not completely replace traditional microbiological techniques but will help to identify, monitor, and isolate important organisms in wastewater systems (24,30).…”
Section: Discussionmentioning
confidence: 99%
“…Many efforts have been made towards better understanding of the mechanisms controlling the microbial ecology of these systems (Amann et al, 1995(Amann et al, , 1998Wagner et al, 2002;Daims et al, 2006;Martín et al, 2006). However, little is known about phage activity in bioreactors, a subject considered, thus far, in only a handful of publications (Ewert and Paynter, 1980;Hantula et al, 1991;Khan et al, 2002a, b;Otawa et al, 2007;Kunin et al, 2008;Wu and Liu, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that the complex structure of activated sludge systems is difficult to assess with traditional techniques (4,5). The emerging molecular techniques used to investigate systems in situ may not completely replace traditional microbiological techniques but will help to identify, monitor, and isolate particular organisms in wastewater systems (6,7).…”
mentioning
confidence: 99%